2020
DOI: 10.1080/21645515.2020.1714311
|View full text |Cite
|
Sign up to set email alerts
|

Twitter as a sentinel tool to monitor public opinion on vaccination: an opinion mining analysis from September 2016 to August 2017 in Italy

Abstract: Social media have become a common way for people to express their personal viewpoints, including sentiments about health topics. We present the results of an opinion mining analysis on vaccination performed on Twitter from September 2016 to August 2017 in Italy. Vaccine-related tweets were automatically classified as against, in favor or neutral in respect of the vaccination topic by means of supervised machine-learning techniques. During this period, we found an increasing trend in the number of tweets on thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
103
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 116 publications
(108 citation statements)
references
References 37 publications
1
103
0
1
Order By: Relevance
“…Basic information about Twitter and the definitions of the Twitter terms mentioned in this article can be found in Appendix A . Published articles about opinion analysis towards vaccination on social media usually perform short-term SA [ 9 , 24 , 25 ] in small datasets [ 24 , 26 ]. Some studies are limited to a single location [ 24 , 25 , 27 ], but usually geolocation is not analysed [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Basic information about Twitter and the definitions of the Twitter terms mentioned in this article can be found in Appendix A . Published articles about opinion analysis towards vaccination on social media usually perform short-term SA [ 9 , 24 , 25 ] in small datasets [ 24 , 26 ]. Some studies are limited to a single location [ 24 , 25 , 27 ], but usually geolocation is not analysed [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…Published articles about opinion analysis towards vaccination on social media usually perform short-term SA [ 9 , 24 , 25 ] in small datasets [ 24 , 26 ]. Some studies are limited to a single location [ 24 , 25 , 27 ], but usually geolocation is not analysed [ 3 ]. In our research, we aim to evaluate public perceptions regarding vaccination on Twitter by performing a sentence-level SA on a dataset composed of 1,499,227 vaccine-related tweets, in English and Spanish, published from June 2011 to April 2019.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, Twitter can be used as a tool to assess the general state of events, such as the COVID-19 pandemic and its effect on the mental health of pregnant women and mothers [ 29 ]. There are multiple approaches to gather and analyze data from Twitter according to the research subject and keywords [ 30 , 31 ]. Some approaches utilize supervised machine learning to limit human error in finding tweets of interest [ 30 ].…”
Section: Introductionmentioning
confidence: 99%
“…There are multiple approaches to gather and analyze data from Twitter according to the research subject and keywords [ 30 , 31 ]. Some approaches utilize supervised machine learning to limit human error in finding tweets of interest [ 30 ]. Other approaches use automated data analysis and clustering techniques that allows for easy and efficient subject grouping [ 31 ].…”
Section: Introductionmentioning
confidence: 99%
“…Twitter has been increasingly used as a data source for health-related research, offering a more e cient means of data collection over traditional survey methods [2].For instance, it has been used to examine disease stigma [3], and to monitor disease pandemics [4] [5]. More recent studies have used Twitter data for the assessment of public sentiments, attitudes and opinions about health related issues [6] [7]. These studies have shown that there may be scope for using Twitter generated data to provide insight about the public opinion on the current COVID-19 pandemic.…”
Section: Introductionmentioning
confidence: 99%